PROTECTION OF THE RIGHTS OF SUSPECTS DURING THE INVESTIGATION STAGE ACCORDING TO THE KUHAP - Aulia Rahman Hakim Hasibuan; Muhammad Ikhsan Surbakti (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This paper critically examines the legal protection provided to suspects during the investigation phase under the Criminal Procedure Code (KUHAP), and exposes the gaping gap between normative provisions and actual practice. The KUHAP contains a series of fundamental rights for suspects, such as the right to information about the charges, the right not to be tortured, the right to remain silent, and the right to legal counsel from the outset of the legal process. However, reality shows that these articles often serve more as empty slogans than as truly protected norms. This research uses a normative juridical approach and is supported by empirical data from institutions such as Komnas HAM, LBH, and KontraS, which prove that violations of suspects' rights, particularly in the form of torture and restrictions on legal aid, have become a systemic and recurring practice. Law enforcement officials knowingly violate the principle of legality and human rights principles, while the state allows these violations to continue without effective control. Law enforcement in Indonesia is currently in danger of decadence, where legal instruments are used only to strengthen power, rather than guarantee justice. The Criminal Procedure Code, which should serve as a shield of protection, is often misused as a tool of repression. Without structural reform and the political courage to firmly address violations, this country is not enforcing the law, but rather producing institutionalized injustice. It's time to stop being lenient on human rights violations by the authorities and start demanding the strict implementation of every norm of the Criminal Procedure Code. Criminal procedure law must not be subject to the logic of power. It must return to the people, as a tool of protection, not a snare that silences.